Studi Literatur Komunikasi Matematis, Self Efficacy, Model Pembelajaran Trefinger dan Asessmen Kinerja - Puji Nurhayati; St. Budi Waluya; Mohammad Asikin; Zaenuri (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Mathematical communication is needed by people to communicate ideas or solving mathematical problems, either orally, in writing, or visually, both in learning mathematics and outside learning mathematics. Mathematical communication skills can be viewed from several aspects, one of which is self-efficacy which affects student success. In addition to mathematical communication, self-efficacy or self-confidence in one's ability to communicate ideas simultaneously has an influence on learning achievement. The teacher also uses a learning model, namely the Trefinger learning model. This model uses divergent thinking along with the ability to apply the concepts that have been learned. In addition, the teacher also uses a performance assessment, with a performance assessment an assessment will be carried out on student activities as it happened.